2022
DOI: 10.1021/jacs.1c13377
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Insights into Cation-Coupled Electron Hopping Transport in a Metal–Organic Framework

Abstract: Electron transport through metal−organic frameworks by a hopping mechanism between discrete redox active sites is coupled to diffusionmigration of charge-balancing counter cations. Experimentally determined apparent diffusion coefficients, D e app , that characterize this form of charge transport thus contain contributions from both processes. While this is well established for MOFs, microscopic descriptions of this process are largely lacking. Herein, we systematically lay out different scenarios for cation-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…47 Given that the Fe and Zn systems are isostructural, the substantial difference in conductivity likely arises from the materials possessing distinct transport mechanisms. For the Zn system, redox hopping between clusters necessitates ion movement to maintain charge neutrality, 29,[52][53][54][55][56] whereas charge carrier delocalization in the Fe system maintains charge neutrality through motion of both electrons and holes.…”
Section: Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…47 Given that the Fe and Zn systems are isostructural, the substantial difference in conductivity likely arises from the materials possessing distinct transport mechanisms. For the Zn system, redox hopping between clusters necessitates ion movement to maintain charge neutrality, 29,[52][53][54][55][56] whereas charge carrier delocalization in the Fe system maintains charge neutrality through motion of both electrons and holes.…”
Section: Results and Analysismentioning
confidence: 99%
“…For example, conductivity studies of the MOF Zr(3-hydroxy-2-[7-(4carboxy-2-hydroxyphenyl)-1,3,6,8-tetraoxo-3,6,7,8-tetrahydro-1H-benzo[lmn] [3,8]phenanthrolin-2-yl]benzoate) revealed that diffusion coefficients derived from chronoamperometry decreased with higher dielectric solvents. 29 However, the scope of the study was limited to few solvents and focused on just this hopping-type material. However, anecdotal evidence abounds for the solvent-and electrolyte-dependence of charge transport in large-pore MOFs and COFs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations